2022
DOI: 10.33225/jbse/22.21.1143
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry and Project-Based Learning as an Approach for Developing Entrepreneurship Competencies in Primary School High-Achieving Students

Abstract: Development of entrepreneurial capacities, entrepreneurial mindset and entrepreneurial culture among students is one of the goals of modern education. In Serbia, there is an idea and vision of entrepreneurial education in the chemistry domain, which is also regulated by the curriculum. Despite these facts, a curriculum that supports entrepreneurship and a large scope for chemistry entrepreneurship, primary schools still lack in activities that could develop competencies related to entrepreneurship in students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…By the application of learning that integrates PjBL models with plant growth and development material, students are able to carry out bioentrepreneurship activities well. In various previous studies, PjBL was also reported to have a significant effect on improving students' entrepreneurial skills (Divac et al, 2022;Elfayetti et al, 2023). Through this model, students can improve competencies related to entrepreneurship, such as entrepreneurial spirit, entrepreneurial culture, and entrepreneurial capacity (Wang et al, 2022).…”
Section: Figure 5 Readability Test Resultsmentioning
confidence: 82%
“…By the application of learning that integrates PjBL models with plant growth and development material, students are able to carry out bioentrepreneurship activities well. In various previous studies, PjBL was also reported to have a significant effect on improving students' entrepreneurial skills (Divac et al, 2022;Elfayetti et al, 2023). Through this model, students can improve competencies related to entrepreneurship, such as entrepreneurial spirit, entrepreneurial culture, and entrepreneurial capacity (Wang et al, 2022).…”
Section: Figure 5 Readability Test Resultsmentioning
confidence: 82%
“…Sekolah dasar sebagai jenjang yang paling dasar dirasa tepat untuk diterapkan pembelajaran kewirausahaan (Barnawi & Arifin, 2012). Di tingkat sekolah dasar, anak-anak berada pada usia yang optimal untuk menginternalisasi nilai-nilai dasar kewirausahaan seperti kreativitas, kepercayaan diri, kerja keras, dan ketekunan (Hardiyat et al, 2023;Floris et al, 2023;Divac et al, 2022). Program pendidikan kewirausahaan di sekolah dasar telah terbukti dalam meningkatkan kompetensi pemecahan masalah, keterampilan komunikasi, kreativitas, kepemimpinan, dan keterampilan eksekusi di antara peserta didik, mempersiapkan mereka untuk menghadapi tantangan masyarakat di masa depan (Moon et al, 2023).…”
Section: Pendahuluanunclassified